Estudio de la prevalencia de diarrea viral bovina en ganaderías del cantón Saraguro, provincia de Loja - González Carbajal, Kleber Jairo (2016)
This following research work was done in Saraguro canton, province of Loja, Ecuador with the aim of determining the prevalence of the virus of the bovine viral diarrhea (BVDV) in dairy cows. The number of samples was of 154, for the detection of antibodies against BVDV in milk by the indirect ELISA test. It was concidered the frequency of each of the variables obtained, in which a prevalence of 27.92% was determined of Saraguro canton; the parish with the highest percentage of BVDV has a 66.67 %: cows ≥ 8 years old had a percentage of 35.71%; 3 to 4 births showed a high percentage of positivity with 31.75%; the Jersey cows showed a high percentage of positivity with 66.67%; in the semi-extensive management systems it had the highest percentage of positivity with 33.63%; farms with biosafety standards had obtained a percentage of 40%; cows inseminated were the largest percentage of positivity obtained with 40%; when it comes to clinical signs animals that had diarrhea and abortions were positive for showing antibodies of DVB with a percentage of 100%.